Sumber Daya Manusia (Fitrah, Akal, Qalb, dan Nafs) dalam Filsafat Pendidikan Islam - Fadillah, Muti'ah; Maragustam (IAIN Ponorogo, 2024)
Human resources are an important aspect of exploring the philosophy of Islamic education. Human potential can be synthesized in the world of education, and its development leads to the realm of contemporary education. This makes human resources something that must be examined. To produce novelty in contemporary Islamic education. The data analysis technique uses a deductive descriptive method by examining various sources by synthesizing from general to specific. The results of this study are fitrah innate from birth in a holy manner, reason is a process of critical thinking power, qalb the last filter process of the thinking process in other words self-purity, nafs tendency to positive morals with proper and accurate control. Its development is through education, teaching, and ta'dib. While the relevance of human potential is to produce integrated scientific curriculum products.